A United Nations High Commissioner for Human Rights - Clark, Roger Stenson. author. aut Link
186 p. 1 illus.
Keywords: prospects of the High Commissioner proposal with careful scholarship and shrewd judgment. Mr. Clark wrote the first draft of this book under my supervision for the degree of Doctor of the Science of Law at Columbia Law School before returning to take up his career as a law teacher in his native New Zealand. I am delighted that his work, in this improved and updated version, is now being published. It fills a real need, since it is the first book on this important subject. On this occasion it might be appropriate to add a few comments on the history of the High Commissioner proposal. As Mr. Clark indicates, I had something to do with its "revival" in the United States Government during the closing months of the Kennedy Administration. A few details as to how this "revival" took place may perhaps be useful to students of international relations and international organization.